REPRODUCTIVE BIOLOGY OF THE MULLET LIZA FALCIPINNIS (VALENCIENNES, 1836) IN TWO AFRICAN COMPLEXS LAGOONS (EBRIÉ AND GRAND-LAHOU) (CÔTE D’IVOIRE) - Gervais, Ebram Luc; SYLLA, Soumaïla; ZAN-BI, Tizié Thierry; ATSE, Boua Célestin (International Journal of Research -GRANTHAALAYAH, 2018)
The reproduction of Liza falcipinnis were investigated in both lagoons (Ebrié and Grand-Lahou) from January 2006 to december 2007. 2162 specimens were examined (914 and 1248 respectively in Ebrié and Grand-Lahou lagoons). Fork length was taken to the nearest 1 mm, and total body weight (TW) and eviscerated body weight (EW) to the nearest 0.1 g. The gonads and the liver were then established removed, weighted to the nearest 0.001g. The reproduced period of Liza falcipinnis was established by analysing the temporal evolution of the frequency of the maturity stages and the monthly variations in the gonadosomatic index (GSI), the hepatosomatic index (HIS) and the condition factor (K). Sex ratio was established taking into account the sex determinations. The size at which 50 % of the specimens became mature (FL50) was estimated. The sex ratio (1:1.24) and (1:1.40) observed respectively in Ebrié and Grand-Lahou lagoons were in favour of females. The first sexual maturity size was 21.0 cm (FL) for males and 27.9 cm (FL) for females in Ebrié lagoon and 24.7 cm (FL) for males and 27.9 cm (FL) for females in Grand-Lahou lagoon. Liza falcipinnis spawns in lagoon and the spawning period ranged from December to April.